Studi Awal Pemberian Mikoriza untuk Mengendalikan Penyakit Layu Fusarium Pisang - Muhamad Rohman Bukhori; Rida Oktorida Khastini; Nani Maryani (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2020)
Banana is the number one fruit commodity in Indonesia. Thousands of household farmers depend on their income in cultivating banana on their back-home yard. However, banana is under threat of fusarium wilt disease that cannot be eliminated using fungicides. In this research, we aimed to examine the effect of mycorrhizal fungi on plants in controlling fusarium wilt. We used, two local banana varieties Raja Buluh and Kepok Kuning. The experiment was design using complete random design two factors. The plants were kept in well-controlled green house. Supplementation of mycorrhizal fungi on those two varieties increase the growth of the pseudostem. Pisang Raja Buluh which colonized by mycorrhizal fungi were resistant to fusarium wilt, but not on pisang Kepok Kuning. This research give insight on the use of mycorrhizal fungi to control fusarium wilt on bananas. Further studies with larger samples and more varieties that are susceptible will be interesting and important to find effective methods to control this important disease on bananas